AN ANALYSIS OF THE HATRED REFLECTED IN AGATHA CHRISTIE'S NOVEL "APPOINTMENT WITH DEATH" - Ratna Sari Dewi (PHILOLOGY Journal of English Language and Literature, 2021)
This research discusses hatred of the characters based on Agatha Christie's novel "Appointment with Death”. Hatred of the characters to the protagonist of this novel. That is mrs. Boynton is the study of this writing. She is a sadist, happy to see someone suffer because of her actions. It gives a great pleasure for her. However, hatred comes to her from the people around such as, her children, her daughter-in-law and her colleagues. In the end of this story, Mrs. Boynton gets a final result of her attitude. She is killed by a person who has become a victim of Mrs. Boynton's brutality. The analysis is focused on hatred in Agatha Christie Novel “Appointment with Death”. The analysis covers only hatred of the main characters. This research uses descriptive qualitative method to an analysis of the hatred reflected in agatha christie's novel "appointment with death".